2008
DOI: 10.1007/978-3-540-88564-1_32
|View full text |Cite
|
Sign up to set email alerts
|

RDFS Reasoning and Query Answering on Top of DHTs

Abstract: We study the problem of distributed RDFS reasoning and query answering on top of distributed hash tables. Scalable, distributed RDFS reasoning is an essential functionality for providing the scalability and performance that large-scale Semantic Web applications require. Our goal in this paper is to compare and evaluate two well-known approaches to RDFS reasoning, namely backward and forward chaining, on top of distributed hash tables. We show how to implement both algorithms on top of the distributed hash tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 18 publications
1
71
0
Order By: Relevance
“…4sr does not materialize any entailments in the assertion phase, therefore the import throughput we obtained when importing the LUBM datasets is similar to the figures reported by 4store developers, around 100kT/s for the cluster set-up and 114kT/s for the server set-up 6 .…”
Section: Lubm Scalability Evaluationsupporting
confidence: 71%
See 1 more Smart Citation
“…4sr does not materialize any entailments in the assertion phase, therefore the import throughput we obtained when importing the LUBM datasets is similar to the figures reported by 4store developers, around 100kT/s for the cluster set-up and 114kT/s for the server set-up 6 .…”
Section: Lubm Scalability Evaluationsupporting
confidence: 71%
“…To date, there has been little progress on distributed backward chained reasoning for triple stores. [6] presented an implementation on top of DHTs using p2p techniques. So far, such solutions have not provided the community with tools, and recent investigations have concluded that due to load balancing issues they cannot scale [7].…”
Section: Related Workmentioning
confidence: 99%
“…Several proposed techniques are based on deterministic rendezvous-peers on top of distributed hashtables [1,2,4,9]. However, because of load-balancing problems due to the data distributions, these approaches do not scale [10].…”
Section: Related Workmentioning
confidence: 99%
“…An embarrassingly parallel algorithm is used in [27] for computing the RDFS closure. In [9], distributed hash tables were used for the computation of RDFS closure. Soma et al [23] investigate two partitioning approaches for parallel inferencing in OWL Horst.…”
Section: Related Workmentioning
confidence: 99%